2013
DOI: 10.1007/s11046-012-9610-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of Voriconazole for the Treatment of Paecilomyces lilacinus Cutaneous Infections: Case Presentation and Review of Published Literature

Abstract: The fungus Paecilomyces lilacinus is a rare but emerging pathogen that causes severe human infections, especially in immunocompromised hosts. It is an important organism to identify due to its poor susceptibility to conventional antifungal drugs, including amphotericin B, itraconazole, and fluconazole. Oculomycosis and cutaneous infections are the two most common manifestations of P. lilacinus infections. Voriconazole has been used successfully to treat P. lilacinus endophthalmitis, but reports of skin and sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 10 publications
0
22
0
1
Order By: Relevance
“…Indeed, the triazolic system can be replaced by a benzotriazole ring, in order to evaluate the effects of the bioisosteric replacement on the biological behavior. Concerning the mechanism of action, it is known that antimycotic drugs, such as fluconazole [66], itraconazole [67], voriconazole [68], ravuconazole [69] and posaconazole [70] exert their pharmacological action by inhibiting the fungal 14 a-demethylase cytochrome P450. Known as CYP51, this is an essential enzyme in the biosynthesis of sterols.…”
Section: Benzotriazole As Antimycotic Agentmentioning
confidence: 99%
“…Indeed, the triazolic system can be replaced by a benzotriazole ring, in order to evaluate the effects of the bioisosteric replacement on the biological behavior. Concerning the mechanism of action, it is known that antimycotic drugs, such as fluconazole [66], itraconazole [67], voriconazole [68], ravuconazole [69] and posaconazole [70] exert their pharmacological action by inhibiting the fungal 14 a-demethylase cytochrome P450. Known as CYP51, this is an essential enzyme in the biosynthesis of sterols.…”
Section: Benzotriazole As Antimycotic Agentmentioning
confidence: 99%
“…Toshio DEMITSU, 1 Kazutaka NAGASHIMA, 1 Taro OKABE, 2 Yuji MORISAWA, 2 Nobuo ISHIKAWA, 3 Takashi YAGISAWA, 3 Hirotaka FUKUTA, 4 Mamitaro OHTSUKI, 4 Rui KANO, 5 Kazutoshi HARADA 6…”
Section: Conflict Of Interest: None Declaredmentioning
confidence: 99%
“…1 P. lilacinum is an airborne and soil fungi with little virulence and may affect immunocompromised hosts causing cutaneous deep mycosis as well as oculomycosis. 1,3,4 Ezzendin et al 5 suggested the usefulness of the antifungal susceptibility testing. 2 Twelve patients had underlying disorders, which might have caused immunosuppression.…”
mentioning
confidence: 99%
See 2 more Smart Citations